Security and online social networks - Echaiz, Javier (2009)
In the last few years we have witnessed a sustained rise in the popularity of online Social Network Sites (SNSs) such as Twitter, Facebook, Myspace, Flickr, LinkedIn, FriendFeed, Google Friend Con- nect, Yahoo! Groups, etc., which are some of the most visited websites worldwide. However, since they are are easy to use and the users are often not aware of the nature of the access of their profiles, they often reveal information which should be kept away from the public eyes. As a result, these social sites may originate security related threats for their members. This paper highlights the benefits of safe use of SNSs and emphasizes the most important threats to members of SNSs. Moreover, we will show the main factors behind these threats. Finally we present policy and technical recommendations in order to improve security without compromising the benefits of information sharing through SNSs.